FOXA1 mediates p16INK4a activation during cellular senescence. (26th February 2013) - Li, Qian; Zhang, Yu; Fu, Jingxuan; Han, Limin; Xue, Lixiang; Lv, Cuicui; Wang, Pan; Li, Guodong; Tong, Tanjun
<x xml:space="preserve">Abstract</x> Mechanisms governing the transcription of p16INK4a, one of the master regulators of cellular senescence, have been extensively studied. However, little is known about chromatin dynamics taking place at its promoter and distal enhancer. Here, we report that Forkhead box A1 protein (FOXA1) is significantly upregulated in both replicative and oncogene‐induced senescence, and in turn activates transcription of p16INK4a through multiple mechanisms. In addition to acting as a classic sequence‐specific transcriptional activator, FOXA1 binding leads to a decrease in nucleosome density at the p16INK4a promoter in senescent fibroblasts. Moreover, FOXA1, itself a direct target of Polycomb‐mediated repression, antagonizes Polycomb function at the p16INK4a locus. Finally, a systematic survey of putative FOXA1 binding sites in the p16INK4a genomic region revealed an ∼150 kb distal element that could loop back to the promoter and potentiate p16INK4a expression. Overall, our findings establish several mechanisms by which FOXA1 controls p16INK4a expression during cellular senescence.